ANALISIS PERTIMBANGAN HAKIM TERKAIT PUTUSAN EKSEKUSI SENGKETA TANAH PADA PANGKALAN TNI AU TERHADAP TOKOH MASYARAKAT KABUPATEN TULANG BAWANG (Studi Putusan Nomor 32/Pdt.Plw/2020/PN.Mgl) - Gilang Adivia Ramadan; Recca Ayu Hapsari; Yulia Hesti (Case Law : Journal of Law, 2022)
A civil dispute is a civil case that occurs between the disputing parties in which it contains a dispute that must be resolved by both parties. If one of the parties feels that their rights have been violated or harmed by the other party, then the party who feels that their rights have been violated or harmed can file a lawsuit or claim their rights legally through the Judiciary. Land disputes occur when the parties do not want to settle the case peacefully, they can resolve it by submitting the case to the District Court. The research method uses a normative and empirical juridical approach. The types of data used are secondary data and primary data. Collecting data through library research (library research) and field research (field research). The data analysis used is juridical qualitative. The judge's considerations in determining the decision regarding the execution of land in decision Number 32/Pdt.Plw/2020/PN Mgl, he parties in a case must be clear, so that later when the decision has become legally binding there will no longer be any basis from the Panel of Judges against the party who filed resistance to an execution because in the first case the Panel of Judges has decided that the party who is said to be in control of the object of execution does not only control the object of execution. the defendant, there is a need for harmony to be taken into consideration in deciding which parties should be the subject of a case.